LANDSHAFTLARNI QISHLOQ XO‘JALIK MAQSADLARIDA TADQIQ ETISHNING NAZARIY ASOSLARI - Yarashev, Q.S.; Xasanov, P.A. (SCIENCE and SOCIETY, 2024)
In the study of landscapes for agricultural purposes, the introduction of natural processes into a certain rhythm helps to find solutions to current problems.
Keywords: landscape; agriculture; agrolandscape; desertification; salinization; natural landscape; modification; anthropogenic; theoretical